Menggali Keutamaan Al-Qur’an Sumber Petunjuk Dalam Kehidupan Umat Islam - Sifa Hayatul Husna; Elsita Insani; Najwa Ananda Putri; Sabila Ramadani Lubis; Latifha Umi Barokha; Wismanto Wismanto (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
This study aims to determine that the Qur'an as the holy book of Muslims plays an important role in guiding daily behavior and actions. In the context of modern life full of challenges, a deep understanding of the Qur'an as the main source of guidance is very crucial to shape the character and moral values ​​of Muslims. The purpose of this study is to explore the primacy of the Qur'an as the main source of guidance in the lives of Muslims. The method used for the study on "DIGGING INTO THE PRINCIPLES OF THE Qur'an: THE MAIN SOURCE OF GUIDANCE IN THE LIVES OF ISLAMIC PEOPLE" uses a qualitative approach with a literature study method, which involves the analysis of the texts of the Qur'an and related literature, including interpretations from scholars and previous research. Data are analyzed thematically to identify the basic principles contained in the Qur'an and their application in daily life. This study aims to examine the role of the Qur'an as the main source of guidance in the lives of Muslims, as well as to explore the application of its teachings in social, economic, and spiritual contexts. The results of this study indicate that the Qur'an provides comprehensive guidance for Muslims in various aspects of life. The teachings of the Qur'an on justice, compassion, and social responsibility have proven to be a strong foundation in building a harmonious society. In addition, this study underlines the importance of contextual understanding of the teachings of the Qur'an in order to be relevant to the challenges of today's era.